Inhibitory activity against ?-amylase and ?-glucosidase by phenolic compounds of quinoa (Chenopodium quinoa Willd.) and cañihua (Chenopodium pallidicaule Aellen) from the Andean region of Peru - Coronado-Olano J. (2021)
This study was funded by a grant from the National Fund for Scientific, Technological Development and Technological Innovation (FONDECYT) of the National Council of Science, Technology and Technological Innovation (CONCYTEC) of Peru, Contract N° 171-2015-FONDECYT.